2013
DOI: 10.1098/rsfs.2012.0067
|View full text |Cite
|
Sign up to set email alerts
|

A novel computational sheep atria model for the study of atrial fibrillation

Abstract: One contribution of 25 to a Theme Issue 'The virtual physiological human: integrative approaches to computational biomedicine'. Sheep are often used as animal models for experimental studies into the underlying mechanisms of cardiac arrhythmias. Previous studies have shown that biophysically detailed computer models of the heart provide a powerful alternative to experimental animal models for underpinning such mechanisms. In this study, we have developed a family of mathematical models for the electrical actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 38 publications
4
41
0
1
Order By: Relevance
“…Shorter APDs in the PV than in the LA also agree with the experimental data [13]. Detailed comparisons between the AP characteristics simulated using the PV and LA models and measured experimentally can be found elsewhere [11,23].…”
Section: Cell Electrophysiologysupporting
confidence: 74%
See 1 more Smart Citation
“…Shorter APDs in the PV than in the LA also agree with the experimental data [13]. Detailed comparisons between the AP characteristics simulated using the PV and LA models and measured experimentally can be found elsewhere [11,23].…”
Section: Cell Electrophysiologysupporting
confidence: 74%
“…Note also that the PV sleeves were segmented based on a histology-guided computational approach under the assumption that conduction pathways in the PVs are similar across species. Under this assumption, waves propagating with similar velocities in our canine model and the respective histology-based model of sheep atria [15,23] will cover a similar area over a similar time T act (see §2). The resultant PV segmentation in the canine model (figure 1b,c) agrees with histological [15] and anatomical [17] data, but needs further validation.…”
Section: Limitationsmentioning
confidence: 99%
“…We used a set of cellular models of sheep atrial myocytes developed by Butters et al [8] that took into considerations of the intrinsic electrophysiological Table 1) under HF based on the experiment data of the sheep [3]. As data from sheep may be incomplete, we also assumed similar changes of ICaL, Ito, IKs and INCX as shown in canine HF atrial cells [4,5] as shown in cases of HF-2 and HF-3 in Table 1.…”
Section: Atrial Cell Models With Hf-induced Electrical Remodelingmentioning
confidence: 99%
“…The anatomically accurate and biophysically detailed 3D model of the sheep atria developed by Butters et al [8] was used in this study. In order to run the simulation of the 3D whole atrial model, we adopted the efficient GPU CUDA algorithm developed by Xia et al [9].…”
Section: Gpu-based 3d Sheep Atrial Model and Analysis Of Apd Distribumentioning
confidence: 99%
See 1 more Smart Citation